Trace water mediated growth of oriented single-crystalline mesoporous metal–organic frameworks on gold nanorods. Issue 59 (27th June 2018) - Zhou, Zehao; Li, Mengyuan; Zhao, Jian; Di, Zhenghan; Di, Chunzhi; Liu, Bei; Zhang, Chao; Yan, Chun-Hua; Li, Lele
Abstract : The growth of single-crystalline mesoporous MOFs with well-controlled orientation on the surface of gold nanorods was reported for the first time. Abstract : Here we report, for the first time, the growth of single-crystalline mesoporous MOFs with well-controlled orientation on the surface of gold nanorods. Importantly, it showed that trace amounts of water could induce the formation of MOFs of different phases and shapes, which was critical for the synthesis of such mesoporous heterostructures.